All of Me - Baron, Chris (Christopher Leigh) (New York : Feiwel and Friends, 2019)
Thirteen-year-old Ari faces what it is to be a man while dealing with a cross-country move, his parents' separation, being bullied for his weight, and belatedly starting bar mitzvah preparations.
Keywords: Novels in verse; Body image -- Juvenile fiction; Overweight children -- Juvenile fiction; Jews -- Juvenile fiction -- United States; Bar mitzvah -- Juvenile fiction; Bullying -- Juvenile fiction; Dysfunctional families -- Juvenile fiction; Moving, Household -- Juvenile fiction; Novels in verse; Body image -- Fiction; Overweight persons -- Fiction; Jews -- Fiction -- United States; Bar mitzvah -- Fiction; Bullying -- Fiction; Family problems -- Fiction; Moving, Household -- Fiction; Novels in verse